Modelo de gestión de proyectos arquitectónicos basado en áreas urbanas - Alvarez-Grijalba, Issabeau Priscilla (Instituto Tecnológico de Costa Rica., 2019)
The following research is developed in order to establish a management model of architectural projects based on urban areas of the Greater Metropolitan Area, especially for projects located in neighborhoods outside the four cantons and towards the periphery, within the ring of containment of the GAM. The final result will be an architectural project management model based on information collected from urban areas. The aim is to determine the relationship between the project and the surrounding urban spaces, according to the type of architectural project. The value of this research lies in generating a management model that allows the professional in architecture to streamline the processes of approach and development of architectural projects, especially in small-scale buildings. Finally, this research is an instrument of primary academic use, which will allow the student to transition to his professional life in a more conscious way and will generate more responsible design processes on the part of future professionals.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2019.
Keywords: Costa Rica Gran Área Metropolitana; Proyectos arquitectónicos; Recuperación urbana; Urbanismo